Master batch for release and self-release base film prepared from master batch
By using a release masterbatch composed of esterides, inorganic particles, silicone oil, etc., the prepared self-release base film solves the problem of silicone oil migration in the existing PET release film, and achieves better release force performance and cost-effective.
Patent Information
- Application Number
- CN202510011921.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
After use, the existing PET release film will migrate to the patch, affecting the surface performance of the patch.
A masterbatch for release is adopted, which consists of esterified compounds, inorganic particles, silicone oil, modified polyolefins, graft copolymers, multiblock polymers and tackifiers, and is prepared by an esterification and polycondensation process. Improve the release force performance of the masterbatch.
The prepared self-release base film has good release force performance, and through the design of the three-layer composite film, the cost of the product is reduced and the problem of silicone oil migration is avoided.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of release films, and in particular to a release masterbatch and a self-release base film prepared using the same. Background Art
[0002] Release film is a film material that is non-sticky or slightly sticky after contacting with specific materials under limited conditions. Currently, most PET release films on the market are PET base films coated with silicone oil or fluorinated silicone oil. However, after the release film prepared in the above manner is used, the silicone oil on the release film will migrate to the object being attached, thereby affecting the surface properties of the object being attached. Summary of the invention
[0003] In order to improve the release force performance of a release film, the present application provides a release masterbatch and a self-release base film prepared using the same.
[0004] In the first aspect, the present application provides a release masterbatch, which adopts the following technical solution: A release masterbatch, wherein the raw materials of the masterbatch include the following components in parts by weight: 90-110 parts of esterified product, 0.2-1.0 parts of inorganic particles, 1-5 parts of silicone oil, 5-15 parts of modified polyolefin, 0.2-3.0 parts of tackifier, 0.2-1.5 parts of graft copolymer, and 0.2-1.5 parts of multi-block polymer; the raw materials of the esterified product include acid, alcohol ester, catalyst, and solvent.
[0005] By adopting the above-mentioned technical scheme, esterification is used as the raw material, and a thickener is added to improve the strength of the masterbatch, so that the obtained masterbatch meets the requirements of the film drawing process, and then the release force performance of the masterbatch can be improved by combining inorganic particles, silicone oil, modified polyolefins, graft copolymers, and multi-block polymers. Therefore, the release film prepared using the masterbatch in this application has better release force.
[0006] In a specific embodiment, the inorganic particles include one or more of mica, barium sulfate, kaolin, titanium dioxide, calcium carbonate, silicon dioxide, talc, and montmorillonite.
[0007] In a specific embodiment, the silicone oil includes one or more of methyl silicone oil, ethyl silicone oil, phenyl silicone oil, methyl hydrogen silicone oil, methylphenyl silicone oil, methylchlorophenyl silicone oil, methylethoxy silicone oil, methyltrifluoropropyl silicone oil, methylvinyl silicone oil, methylhydroxy silicone oil, ethyl hydrogen silicone oil, hydroxyl hydrogen silicone oil, cyanide silicone oil, amino-modified silicone oil, epoxy-modified silicone oil, polyether-modified silicone oil, carboxyl-modified silicone oil, alcohol-hydroxyl-modified silicone oil, phenol-modified silicone oil, and mercapto-modified silicone oil.
[0008] In a specific embodiment, the modified polyolefin includes one or more of modified polypropylene, modified polytetrafluoroethylene, and modified TPX.
[0009] In a specific embodiment, the adhesion promoter includes one or more of oxazoline, isocyanate, pyromellitic anhydride, trimellitic anhydride, and glycidyl ether epoxy compounds.
[0010] In a specific embodiment, the graft copolymer includes one or more of oxamalic anhydride grafted polyolefin, ethylene-acrylic acid copolymer, glycidyl methacrylate grafted polyolefin, polystyrene-g-polylactic acid, and polyolefin-g-polyester.
[0011] In a specific embodiment, the multi-block polymer includes one or more of polyethylene-polybutylene terephthalate, polyethylene-polyethylene glycol, di-tert-butyl malonate, and 4,4'-methylenebis(phenyl isocyanate).
[0012] In a specific embodiment, the method for preparing the masterbatch comprises the following steps: Esterification: adding acid to solvent, stirring and mixing to obtain slurry; adding alcohol ester to solvent, stirring and mixing to obtain alcohol ester liquid; adding catalyst to solvent, stirring and mixing to obtain catalyst liquid; mixing slurry and alcohol ester liquid first, then adding catalyst liquid to carry out esterification reaction to obtain esterified product; wherein the molar ratio of acid to solvent is 1:(1.15-1.7); the molar ratio of alcohol ester to solvent is 1:(1.8-2.4); the weight ratio of catalyst to solvent is 1:(20-100); the weight ratio of the mixed liquid of slurry and alcohol ester liquid to catalyst liquid is (97.9-99.63):(0.37-2.1); Polycondensation: first add inorganic particles, silicone oil, modified polyolefin, graft copolymer, and multi-block polymer to the esterified product, then add it to a pre-polycondensation kettle, evacuate it, and first perform pre-polycondensation to obtain a pre-polycondensation product; then pump the pre-polycondensation product into a final polycondensation kettle, perform final polycondensation to obtain a final polycondensation product, and finally add a tackifier to obtain a melt; Pelletizing: The melt is passed through the casting belt head, through the casting belt, cooled, and pelletized to obtain the masterbatch for release.
[0013] By adopting the above technical scheme, an ester is first prepared by using an acid, an alcohol ester, a catalyst, and a solvent, and then inorganic particles, silicone oil, a modified polyolefin, a graft copolymer, and a multi-block polymer are added to the ester, and a pre-condensation is first performed, and then a final condensation is performed, and a viscosity enhancer is added to the final condensation product to obtain a melt, and finally the melt is cast into a strip, cooled, and pelletized to obtain a masterbatch for release.
[0014] In a specific embodiment, the viscosity of the melt is 0.70 dl / g-0.90 dl / g, the terminal carboxyl content is ≦25 mmol / kg, the melting point is 240° C.-272° C., and the ash content is 0.2%-5.0%.
[0015] In a second aspect, the present application provides a self-release base film, which adopts the following technical solution: A self-release base film comprises two outer layers and an intermediate layer arranged between the two outer layers; the raw materials of the outer layer comprise the release masterbatch and slices, the weight fraction of the masterbatch in the outer layer raw materials is 5%-30%; the slices comprise one or more of PET slices, semi-matt slices, silicon-containing PET slices, and polyester slices.
[0016] By adopting the above technical scheme, the self-release base film made using the release masterbatch in this application has good release force performance; and the design of a three-layer composite film can not only ensure the different release force performance of the product, but also reduce the cost of the product.
[0017] In summary, the present application includes at least one of the following beneficial technical effects: 1. In the present application, the esterified product is used as the raw material, and the tackifier is added to improve the strength of the masterbatch, so that the obtained masterbatch meets the requirements of the film drawing process, and then the inorganic particles, silicone oil, modified polyolefin, graft copolymer, and multi-block polymer are used to improve the release force performance of the obtained masterbatch, so that the release film prepared by using the masterbatch in the present application has a good release force; 2. In the present application, an ester is first prepared by using an acid, an alcohol ester, a catalyst, and a solvent, and then inorganic particles, silicone oil, a modified polyolefin, a graft copolymer, and a multi-block polymer are added to the ester, and a pre-polycondensation is first performed, and then a final polycondensation is performed, and a tackifier is added to the final polycondensation product to obtain a melt, and finally the melt is cast into a strip, cooled, and pelletized to obtain a masterbatch for release; 3. The self-release base film in the present application has good release force performance; and the three-layer composite film design can not only ensure the different release force performance of the product, but also reduce the cost of the product. DETAILED DESCRIPTION
[0018] The present application is further described in detail below with reference to the embodiments.
[0019] All raw materials in the examples can be obtained commercially. Acids include but are not limited to terephthalic acid, isophthalic acid, or a mixture of the two. In the present application, terephthalic acid is preferred. Alcohol esters include but are not limited to a mixture of one or more of ethylene terephthalate, ethylene isophthalate, and ethylene naphthalate. In the present application, ethylene terephthalate is preferred. Solvents include but are not limited to a mixture of one or more of ethylene glycol, neopentyl glycol, propylene glycol, butylene glycol, and 1,4-cyclohexanedimethanol. In the present application, ethylene glycol is preferred. Inorganic particles include but are not limited to a mixture of one or more of mica, barium sulfate, kaolin, titanium dioxide, calcium carbonate, silicon dioxide, talc, and montmorillonite. In the present application, Preferably, it is a mixture of silicon dioxide and talc; silicone oil includes but is not limited to methyl silicone oil, ethyl silicone oil, phenyl silicone oil, methyl hydrogen silicone oil, methylphenyl silicone oil, methylchlorophenyl silicone oil, methylethoxy silicone oil, methyltrifluoropropyl silicone oil, methylvinyl silicone oil, methylhydroxy silicone oil, ethyl hydrogen silicone oil, hydroxyl hydrogen silicone oil, cyanide silicone oil, amino-modified silicone oil, epoxy-modified silicone oil, polyether-modified silicone oil, carboxyl-modified silicone oil, alcohol-hydroxyl-modified silicone oil, phenol-modified silicone oil, mercapto-modified silicone oil, preferably methyl silicone oil in this application; modified polyolefin includes but is not limited to a mixture of one or more of modified polypropylene, modified polytetrafluoroethylene, and modified TPX, and in this application Preferably, it is modified polypropylene, CAS No.: 25722-45-6; the tackifier includes but is not limited to a mixture of one or more of oxazoline, isocyanate, pyromellitic anhydride, trimellitic anhydride, and glycidyl ether epoxy compounds, and isocyanate is preferred in this application; the graft copolymer includes but is not limited to a mixture of one or more of oxamalic anhydride grafted polyolefin, ethylene-acrylic acid copolymer, methacrylate glycidyl ester grafted polyolefin, polystyrene-g-polylactic acid, and polyolefin-g-polyester, and is preferably oxamalic anhydride grafted polyolefin, model MAH-g-POE; the multi-block polymer includes but is not limited to polyethylene-polybutylene terephthalate, polyethylene-polyethylene A mixture of one or more of glycol, di-tert-butyl malonate, and 4,4'-methylenebis(phenyl isocyanate), preferably polyethylene-polybutylene terephthalate, model PE-b-PBT in this application; slices include but are not limited to a mixture of one or more of PET slices, semi-matt slices, silicon-containing PET slices, and polyester slices, preferably polyester slices in this application, and the polyester slices are one of Yizheng Chemical Fiber FG600, Yizheng Chemical Fiber FG604, Yizheng Chemical Fiber FG610, Yizheng Chemical Fiber FG611, Yizheng Chemical Fiber FG612, Yizheng Chemical Fiber FG613, Yizheng Chemical Fiber FG616, Yizheng Chemical Fiber FC510, Liaohua BG80, and Hengli DJ20678A. Example
[0020] Example 1 Embodiment 1 provides a method for preparing a release masterbatch, comprising the following steps: Esterification: Add the solvent to the pulping kettle, then add the acid, stir and mix evenly to obtain a slurry; add the alcohol ester to the solvent, stir and mix evenly to obtain an alcohol ester liquid; add the solvent to the catalyst preparation kettle, then add the catalyst, stir and mix evenly to obtain a catalyst liquid; first mix the slurry and the alcohol ester liquid, then add the catalyst liquid, and then put them into the esterification kettle together, and carry out the esterification reaction at 257°C and 150kPa for 4.5 hours to obtain an esterified product; wherein the molar ratio of the acid to the solvent is 1:1.15; the molar ratio of the alcohol ester to the solvent is 1:1.8; the weight ratio of the catalyst to the solvent is 1:20; the weight ratio of the mixed liquid of the slurry and the alcohol ester liquid to the catalyst liquid is 97.9:2.1; the acid is terephthalic acid; the alcohol ester is ethylene glycol terephthalate; the catalyst is antimony trioxide; the solvent is ethylene glycol; Polycondensation: first add 0.2kg of inorganic particles, 1kg of silicone oil, 5kg of modified polyolefin, 0.2kg of graft copolymer, and 0.2kg of multi-block polymer to 90kg of esterification, then add them to the pre-polycondensation kettle, evacuate, discharge excess solvent, first pre-polycondense at 275℃, 5kPa for 3h to obtain the pre-polycondensation product; then pump the pre-polycondensation product into the final polycondensation kettle, final polycondense at 282℃, 150kPa for 2.5h to obtain the final polycondensation product, and finally add 0.2 kg thickener, and a melt is obtained, and the viscosity of the melt is 0.70 dl / g, the terminal carboxyl content is 15 mmol / kg, the melting point is 240°C, and the ash content is 0.2%; wherein the inorganic particles are a mixture of silicon dioxide and talc, and the weight ratio of silicon dioxide to talc is 1:1; the silicone oil is methyl silicone oil; the modified polyolefin is modified polypropylene; the graft copolymer is maleic anhydride grafted polyolefin; the multi-block polymer is polyethylene-polybutylene terephthalate; and the thickener is isocyanate; Pelletizing: The melt is passed through the casting belt head, through the casting belt, cooled, and pelletized to obtain the masterbatch for release.
[0021] Example 2 Embodiment 2 provides a method for preparing a release masterbatch, comprising the following steps: Esterification: Add the solvent to the pulping kettle, then add the acid, stir and mix evenly to obtain a slurry; add the alcohol ester to the solvent, stir and mix evenly to obtain an alcohol ester liquid; add the solvent to the catalyst preparation kettle, then add the catalyst, stir and mix evenly to obtain a catalyst liquid; first mix the slurry and the alcohol ester liquid, then add the catalyst liquid, and then put them into the esterification kettle together, and carry out the esterification reaction at 257°C and 150kPa for 4.5 hours to obtain an esterified product; wherein the molar ratio of the acid to the solvent is 1:1.15; the molar ratio of the alcohol ester to the solvent is 1:1.8; the weight ratio of the catalyst to the solvent is 1:20; the weight ratio of the mixed liquid of the slurry and the alcohol ester liquid to the catalyst liquid is 97.9:2.1; the acid is terephthalic acid; the alcohol ester is ethylene glycol terephthalate; the catalyst is antimony trioxide; the solvent is ethylene glycol; Polycondensation: First, add 0.6kg of inorganic particles, 3kg of silicone oil, 10kg of modified polyolefin, 0.8kg of graft copolymer, and 0.8kg of multi-block polymer to 100kg of esterification product, then add them to the pre-polycondensation kettle, evacuate, discharge excess solvent, first pre-polycondense for 3h at 275℃ and 5kPa to obtain the pre-polycondensation product; then pump the pre-polycondensation product into the final polycondensation kettle, final polycondense for 2.5h at 282℃ and 150kPa to obtain the final polycondensation product, and finally add 1. 6kg thickener, to obtain a melt, and the melt viscosity is 0.80dl / g, the terminal carboxyl content is 20mmol / kg, the melting point is 256℃, and the ash content is 2.6%; wherein the inorganic particles are a mixture of silicon dioxide and talc, and the weight ratio of silicon dioxide to talc is 1:1; the silicone oil is methyl silicone oil; the modified polyolefin is modified polypropylene; the graft copolymer is maleic anhydride grafted polyolefin; the multi-block polymer is polyethylene-polybutylene terephthalate; the thickener is isocyanate; Pelletizing: The melt is passed through the casting belt head, through the casting belt, cooled, and pelletized to obtain the masterbatch for release.
[0022] Example 3 Embodiment 3 provides a method for preparing a release masterbatch, comprising the following steps: Esterification: Add the solvent to the pulping kettle, then add the acid, stir and mix evenly to obtain a slurry; add the alcohol ester to the solvent, stir and mix evenly to obtain an alcohol ester liquid; add the solvent to the catalyst preparation kettle, then add the catalyst, stir and mix evenly to obtain a catalyst liquid; first mix the slurry and the alcohol ester liquid, then add the catalyst liquid, and then put them into the esterification kettle together, and carry out the esterification reaction at 257°C and 150kPa for 4.5 hours to obtain an esterified product; wherein the molar ratio of the acid to the solvent is 1:1.15; the molar ratio of the alcohol ester to the solvent is 1:1.8; the weight ratio of the catalyst to the solvent is 1:20; the weight ratio of the mixed liquid of the slurry and the alcohol ester liquid to the catalyst liquid is 97.9:2.1; the acid is terephthalic acid; the alcohol ester is ethylene glycol terephthalate; the catalyst is antimony trioxide; the solvent is ethylene glycol; Polycondensation: first add 1kg of inorganic particles, 5kg of silicone oil, 15kg of modified polyolefin, 1.5kg of graft copolymer, and 1.5kg of multi-block polymer to 110kg of esterification, then add to the pre-polycondensation kettle, evacuate, discharge excess solvent, first pre-polycondense at 275℃, 5kPa for 3h to obtain a pre-polycondensation product; then pump the pre-polycondensation product into the final polycondensation kettle, final polycondense at 282℃, 150kPa for 2.5h to obtain a final polycondensation product, and finally add 3k g thickener, and a melt is obtained, and the melt has a viscosity of 0.90 dl / g, a terminal carboxyl content of 25 mmol / kg, a melting point of 272°C, and an ash content of 5.0%; wherein the inorganic particles are a mixture of silicon dioxide and talc, and the weight ratio of silicon dioxide to talc is 1:1; the silicone oil is methyl silicone oil; the modified polyolefin is modified polypropylene; the graft copolymer is maleic anhydride grafted polyolefin; the multi-block polymer is polyethylene-polybutylene terephthalate; and the thickener is isocyanate; Pelletizing: The melt is passed through the casting belt head, through the casting belt, cooled, and pelletized to obtain the masterbatch for release.
[0023] Example 4 The difference between Example 4 and Example 2 is that, for esterification, the solvent is added to a pulping kettle, and then an acid is added, and the mixture is stirred and mixed to obtain a slurry; an alcohol ester is added to a solvent, and the mixture is stirred and mixed to obtain an alcohol ester liquid; the solvent is added to a catalyst preparation kettle, and then a catalyst is added, and the mixture is stirred and mixed to obtain a catalyst liquid; the slurry and the alcohol ester liquid are first mixed, and then the catalyst liquid is added, and then the slurry and the alcohol ester liquid are put into an esterification kettle together, and the esterification reaction is carried out at 257° C. and 150 kPa for 4.5 hours to obtain an esterified product; wherein the molar ratio of the acid to the solvent is 1:1.42; the molar ratio of the alcohol ester to the solvent is 1:2.1; the weight ratio of the catalyst to the solvent is 1:60; the weight ratio of the mixed liquid of the slurry and the alcohol ester liquid to the catalyst liquid is 98.76:1.23; and the remaining steps are consistent with Example 2.
[0024] Example 5 The difference between Example 5 and Example 2 is that, for esterification, the solvent is added to a pulping kettle, and then an acid is added, and the mixture is stirred and mixed to obtain a slurry; an alcohol ester is added to a solvent, and the mixture is stirred and mixed to obtain an alcohol ester liquid; the solvent is added to a catalyst preparation kettle, and then a catalyst is added, and the mixture is stirred and mixed to obtain a catalyst liquid; the slurry and the alcohol ester liquid are first mixed, and then the catalyst liquid is added, and then the slurry and the alcohol ester liquid are put into an esterification kettle together, and the esterification reaction is carried out at 257° C. and 150 kPa for 4.5 hours to obtain an esterified product; wherein the molar ratio of the acid to the solvent is 1:1.7; the molar ratio of the alcohol ester to the solvent is 1:2.4; the weight ratio of the catalyst to the solvent is 1:100; the weight ratio of the mixed liquid of the slurry and the alcohol ester liquid to the catalyst liquid is 99.63:0.37; and the remaining steps are consistent with Example 2.
[0025] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that, polycondensation: first add 0.2 kg of inorganic particles and 1 kg of silicone oil to 95.4 kg of esterification product, then add it to the pre-polycondensation kettle, evacuate, discharge excess solvent, first pre-polycondense at 275 ° C, 5 kPa for 3 hours to obtain a pre-polycondensation product; then pump the pre-polycondensation product into the final polycondensation kettle, and perform final polycondensation at 282 ° C, 150 kPa for 2.5 hours to obtain a final polycondensation product, and finally add 0.2 kg of tackifier to obtain a melt, and the viscosity of the melt is 0.70 dl / g, the terminal carboxyl content is 15 mmol / kg, the melting point is 240 ° C, and the ash content is 0.2%; wherein the inorganic particles are a mixture of silica and talc, and the weight ratio of silica to talc is 1: 1; the tackifier is isocyanate; the remaining steps are consistent with Example 1.
[0026] Application Example 1 Application Example 1 provides a method for preparing a self-release base film, comprising the following steps: The masterbatch and chips in Example 1 are stirred and mixed evenly to obtain an outer layer raw material; wherein the weight fraction of the masterbatch in the outer layer raw material is 5%; and the chips are polyester chips; Polyester chips are selected as the middle layer raw material, and the outer layer raw material and the middle layer raw material are melt-extruded and transported by different extruders, merged by a distributor, and formed into a three-layer structure in front of the extrusion die head, and then cast, longitudinally stretched, transversely stretched, heat-set, corona, and cooled to form. The middle layer raw material forms a middle layer with a thickness of 235 microns, and the outer layer raw material forms an outer layer on both sides of the middle layer with a thickness of 7.5 microns to obtain a self-release base film.
[0027] Application Example 2 The difference between Application Example 2 and Application Example 1 is that the masterbatch is the masterbatch in Example 2, and the remaining steps are consistent with Application Example 1.
[0028] Application Example 3 The difference between Application Example 3 and Application Example 1 is that the masterbatch is the masterbatch in Example 3, and the remaining steps are consistent with Application Example 1.
[0029] Application Example 4 The difference between Application Example 4 and Application Example 1 is that the masterbatch is the masterbatch in Example 4, and the remaining steps are consistent with Application Example 1.
[0030] Application Example 5 The difference between Application Example 5 and Application Example 1 is that the masterbatch is the masterbatch in Example 5, and the remaining steps are consistent with Application Example 1.
[0031] Application Example 6 The difference between Application Example 6 and Application Example 4 is that the weight fraction of the masterbatch in the outer layer raw material is 17.5%, and the remaining steps are consistent with Application Example 4.
[0032] Application Example 7 The difference between Application Example 7 and Application Example 4 is that the weight fraction of the masterbatch in the outer layer raw material is 30%, and the remaining steps are consistent with Application Example 4.
[0033] Application Example 8 The difference between Application Example 8 and Application Example 1 is that the masterbatch is the masterbatch in Comparative Example 1, and the remaining steps are consistent with Application Example 1.
[0034] Release force performance test: According to GBT25256-2010 "Test method for 180° peeling force and residual adhesion rate of release film for optical functional films", the self-release base films in each application example were tested, and the pressure-sensitive tapes used were Tesa 7475 tape and Nitto 31B tape.
[0035] Initial peel force: Attach the tesa 7475 tape to the self-release base film to be tested according to the standard method, and use a density of 70g / cm 2 The standard stainless steel strips were aged at room temperature for 20 hours, cut into long strips according to the shape of the tape, and tested with a release force tester to test the tensile force at a tensile speed of 300 mm / min and a tensile angle of 180°.
[0036] Aging peel strength: tesa 7475 tape was attached to the self-release base film to be tested according to the standard method, and the density was 70g / cm 2 The standard stainless steel strips were pressed in an oven at 70°C for aging for 20 hours, cut into long strips according to the shape of the tape, and tested using a release force tester to test the tensile force at a tensile speed of 300 mm / min and a tensile angle of 180°.
[0037] Residual bonding rate: Step 1, stick Nitto 31B tape on the self-release base film to be tested according to the standard method, and at the same time stick Nitto 31B tape on a blank Teflon according to the standard method as a standard blank sample; and at the same time use a density of 20g / cm 2 The standard stainless steel bars were pressed in an oven at 70°C for 20 h and then taken out and placed at room temperature for 1 h.
[0038] Step 2: tear off the tape from the release film and stick it on a blank PET film. After 1.5 hours, test it with a release force tester. The tensile speed is 300 mm / min. The tensile force at a tensile angle of 180° is the force for peeling off the test tape.
[0039] Step 3, tear off the tape from the blank Teflon and stick it on the blank PET film. After 1.5 hours, use a release force tester to test the tensile force at a stretching speed of 300 mm / min and a stretching angle of 180°, which is the tensile force of the blank standard sample.
[0040] Step 4, residual adhesion rate (%) = average value of the peeled test tape ÷ average value of the blank standard sample × 100%.
[0041] Silicone oil precipitation detection: After staying at 150°C for 15 days, observe the changes in the polyester film under a microscope to see if there is silicone oil precipitation on the surface. If not, the self-release base film has good resistance to silicone oil migration.
[0042] Table 1 Test results of self-release base film sample Initial peel force (g / 25mm) Aging peel strength (g / 25mm) Residual bonding rate (%) Is there any precipitation? Application Example 1 180 200 98 none Application Example 2 175 196 98 none Application Example 3 178 197 98 none Application Example 4 173 193 99 none Application Example 5 175 195 98 none Application Example 6 170 190 99 none Application Example 7 171 190 98 none Application Example 8 215 232 91 have In combination with Application Examples 1-3 and Application Example 8, the peeling force of the self-release base film in Application Example 1-3 is relatively small, and no precipitates appear, so the self-release base film in Application Example 1-3 has good release force performance and good resistance to silicone oil migration. It can be seen that when preparing the masterbatch, silicone oil, modified polyolefins, graft copolymers, and multi-block polymers are added to the raw materials. The combination of these can improve the release force performance of the final self-release base film.
[0043] In combination with Application Example 2, Application Example 4 and Application Example 5, the release force performance of the self-release base film in Application Example 2, Application Example 4 and Application Example 5 is good. It can be seen that when preparing the masterbatch, when conducting the esterification reaction, the molar ratio of acid to solvent is preferably 1: (1.15-1.7); the molar ratio of alcohol ester to solvent is preferably 1: (1.8-2.4); the weight ratio of catalyst to solvent is preferably 1: (20-100); the weight ratio of the mixed liquid of slurry and alcohol ester liquid to catalyst liquid is preferably (97.9-99.63): (0.37-2.1), and the performance of the esterified product is good, thereby improving the release force performance of the self-release base film finally obtained.
[0044] In combination with Application Examples 4, 6 and 7, the release force performance of the self-release base films in Application Examples 4, 6 and 7 is good. It can be seen that when the outer layer raw materials are formulated, when the weight fraction of the masterbatch in the outer layer raw materials is 5%-30%, the final self-release base film has a good release force performance.
[0045] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A release masterbatch, characterized in that: The raw materials of the masterbatch include the following components in parts by weight: 90-110 parts of esterified product, 0.2-1.0 parts of inorganic particles, 1-5 parts of silicone oil, 5-15 parts of modified polyolefin, 0.2-3.0 parts of tackifier, 0.2-1.5 parts of graft copolymer, and 0.2-1.5 parts of multi-block polymer; the raw materials of the esterified product include acid, alcohol ester, catalyst, and solvent.
2. A release masterbatch according to claim 1, characterized in that: The inorganic particles include one or more of mica, barium sulfate, kaolin, titanium dioxide, calcium carbonate, silicon dioxide, talc, and montmorillonite.
3. A release masterbatch according to claim 1, characterized in that: The silicone oil includes one or more of methyl silicone oil, ethyl silicone oil, phenyl silicone oil, methyl hydrogen silicone oil, methyl phenyl silicone oil, methyl chlorophenyl silicone oil, methyl ethoxy silicone oil, methyl trifluoropropyl silicone oil, methyl vinyl silicone oil, methyl hydroxy silicone oil, ethyl hydrogen silicone oil, hydroxy hydrogen silicone oil, cyanide silicone oil, amino-modified silicone oil, epoxy-modified silicone oil, polyether-modified silicone oil, carboxyl-modified silicone oil, alcohol hydroxyl-modified silicone oil, phenol-modified silicone oil, and mercapto-modified silicone oil.
4. The release masterbatch according to claim 1, characterized in that: The modified polyolefin includes one or more of modified polypropylene, modified polytetrafluoroethylene, and modified TPX.
5. The release masterbatch according to claim 1, characterized in that: The tackifier includes one or more of oxazoline, isocyanate, pyromellitic anhydride, trimellitic anhydride, and glycidyl ether epoxy compounds.
6. The release masterbatch according to claim 1, characterized in that: The graft copolymer includes one or more of maleic anhydride grafted polyolefin, ethylene-acrylic acid copolymer, glycidyl methacrylate grafted polyolefin, polystyrene-g-polylactic acid, and polyolefin-g-polyester.
7. The release masterbatch according to claim 1, characterized in that: The multi-block polymer includes one or more of polyethylene-polybutylene terephthalate, polyethylene-polyethylene glycol, di-tert-butyl malonate, and 4,4'-methylenebis(phenyl isocyanate).
8. The release masterbatch according to claim 1, characterized in that: The preparation method of the masterbatch comprises the following steps: Esterification: adding acid to solvent, stirring and mixing to obtain slurry; adding alcohol ester to solvent, stirring and mixing to obtain alcohol ester liquid; adding catalyst to solvent, stirring and mixing to obtain catalyst liquid; mixing slurry and alcohol ester liquid first, then adding catalyst liquid to carry out esterification reaction to obtain esterified product; wherein the molar ratio of acid to solvent is 1:(1.15-1.7); the molar ratio of alcohol ester to solvent is 1:(1.8-2.4); the weight ratio of catalyst to solvent is 1:(20-100); the weight ratio of the mixed liquid of slurry and alcohol ester liquid to catalyst liquid is (97.9-99.63):(0.37-2.1); Polycondensation: first add inorganic particles, silicone oil, modified polyolefin, graft copolymer, and multi-block polymer to the esterified product, then add it to a pre-polycondensation kettle, evacuate it, and first perform pre-polycondensation to obtain a pre-polycondensation product; then pump the pre-polycondensation product into a final polycondensation kettle, perform final polycondensation to obtain a final polycondensation product, and finally add a tackifier to obtain a melt; Pelletizing: The melt is passed through the casting belt head, through the casting belt, cooled, and pelletized to obtain the masterbatch for release.
9. A release masterbatch according to claim 8, characterized in that: The viscosity of the melt is 0.70 dl / g-0.90 dl / g, the terminal carboxyl content is ≤25 mmol / kg, the melting point is 240° C.-272° C., and the ash content is 0.2%-5.0%.
10. A self-release base film, characterized in that: It comprises two outer layers and an intermediate layer arranged between the two outer layers; the raw materials of the outer layers comprise the release masterbatch and slices according to any one of claims 1 to 9, and the weight fraction of the masterbatch in the outer layer raw materials is 5%-30%; the slices comprise one or more of PET slices, semi-matt slices, silicon-containing PET slices, and polyester slices.
Citation Information
Patent Citations
Matt-type high-barrier biaxially-oriented polypropylene cold-seal base film and preparation method thereof
CN109278388A
Polyester master batch special for MLCC release film and preparation method of polyester master batch
CN115322533A
Special master batch for base film of MLCC release film with ABA structure, preparation method of special master batch and base film of MLCC release film
CN117887222A
High-efficiency flame-retardant photovoltaic backboard base film and preparation method thereof
CN118769655A
MLCC release protective film and preparation method thereof
CN119217674A
Cited By
Preparation method of high molecular weight polyester
CN122404686A
A process for the preparation of a high molecular weight polyester
CN122404686B